2004
DOI: 10.1111/j.1468-1331.2003.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological tests and neuroimaging procedures in non‐acute headache: guidelines and recommendations

Abstract: The use of instrumental examinations in headache patients varies widely. In order to evaluate their usefulness, the most common instrumental procedures were evaluated, on the basis of evidence from the literature, by an EFNS Task Force (TF) on neurophysiological tests and imaging procedures in non‐acute headache patients. The conclusions of the TF regarding each technique are expressed in the following guidelines for clinical use. Interictal electroencephalography (EEG) is not routinely indicated in the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 34 publications
0
51
0
5
Order By: Relevance
“…in headache patients varies widely. Recently, a EFNS Task Force evaluated (among other instrumental examination tools) the usefulness of imaging procedures in non-acute headache patients on the basis of evidence from the literature [16 ]. Following these recommendations, in adult and paediatric patients with migraine with no recent change in attack pattern, no history of seizures and no other focal neurological signs or symptoms, the routine use of neuroimaging is not warranted.…”
Section: Diagnostic Imagingmentioning
confidence: 98%
“…in headache patients varies widely. Recently, a EFNS Task Force evaluated (among other instrumental examination tools) the usefulness of imaging procedures in non-acute headache patients on the basis of evidence from the literature [16 ]. Following these recommendations, in adult and paediatric patients with migraine with no recent change in attack pattern, no history of seizures and no other focal neurological signs or symptoms, the routine use of neuroimaging is not warranted.…”
Section: Diagnostic Imagingmentioning
confidence: 98%
“…During the last decade almost every modality of stimulation has been used to study evoked responses in migraine. Various interictal and ictal abnormalities have been reported in migraine, although as yet there are no findings that can be used as a diagnostic tool [7]. We will review the available published data, discuss their findings and examine the possible neurobiological bases of the reported abnormalities.…”
Section: Introductionmentioning
confidence: 96%
“…Previous secondary care studies of consecutive non-acute isolated headache quoted abnormalities for migraine as 0-3.1% and unspecified headache 0-6.7%. 10 A secondary care prospective study suggested that headache without the development of additional signs or symptoms for longer than 11 weeks after initial presentation will only be due to a tumour in exceptional cases. 38 In primary care, if a tumour is present and a headache diagnosis cannot be made at presentation, 74% of tumours will have presented by 3 months, and 90% by 6 months.…”
Section: Box 1 Three Levels Of Risk Of Brain Tumour and Suggested Mamentioning
confidence: 99%